Following the Party in Time of War? The Implications of Elite Consensus. Issue 5 (3rd September 2018) - Wells, Matthew S.; Ryan, Timothy J.
ABSTRACT: Prominent perspectives in the study of conflict point to two factors that exert substantial influence on public opinion about foreign intervention: (1) news about casualties and (2) signals from partisan elites. Past work is limited, however, in what it can say about how these two factors interact. We present an experiment designed to understand the surprisingly common scenario where elites send competing messages about whether the public should support war or oppose it—and these messages do not coincide with party divisions. We find that partisans are generally insensitive to news about casualties, but they become noticeably more sensitive when they perceive within-party disputes over support for the war. Independents, however, respond to news of casualties irrespective of what messages elites send. These findings shed light on when and how the public responds to competing and unclear cues and speak to the role of public opinion in determining conflict outcomes and democratic foreign policy-making more broadly.